On Applications of Fuzzy Soft and Intuitionistic Fuzzy Soft Sets in Dimension Reduction and Medical Diagnosis - Hooda, D. S. (New Ideas Concerning Science and Technology Vol. 8, 2021)
In our daily life, we often come across various problems related to the high dimensionality of data. In such type of problems irrelevant and superfluous data along with useful data is also present. Thus, dimensionality reduction has found wide applications in data analysis and management. In recent years the issue of dimensionality reduction in a fuzzy situation has also gained importance and has invited attention of researchers. The various techniques and theories have been developed by them to solve these types of problems. Some of these techniques based on probabilistic approach and others are non-probabilistic approach. For finding coherent and logical solution to various real life problems containing uncertainty, impreciseness and vagueness, fuzzy soft set theory is gaining significance. Recently, on a theoretical study of intuitionistic fuzzy soft has also been developed. The combination of intuitionistic fuzzy set and intuitionistic fuzzy soft set are more useful for application point of view in the environment when uncertainty due to vagueness is more complex. In this chapter the concept of fuzzy soft set is defined as hybridization of fuzzy set and soft set theory. A new technique is proposed to convert the soft set table into fuzzy soft set table, which is applied in dimension reduction of big data. The concepts of fuzzy soft set and intuitionistic fuzzy soft set are defined as hybridization of fuzzy set and soft set theory. New methods of applications of fuzzy soft and intuitionistic soft sets are also described in Medical Diagnosis following Sanchez’s approach.